Pengeroyokan oleh Pelaku Balap Liar terhadap Anggota Kepolisian di Wilayah Hukum Polres Sidoarjo - Arradhin Daffa Alghifari; Sholehuddin Sholehuddin (DE RECHT (Journal of Police and Law Enforcement), 2025)
Illegal racing represents a form of juvenile delinquency that generates public concern and endangers road users’ safety. Despite regulation under Law Number 22 of 2009 concerning Road Traffic and Transportation, illegal racing practices remain prevalent in Sidoarjo City. Street racing activities not only violate traffic regulations but frequently escalate into various other serious criminal acts. This study employed a juridical-empirical research method, prioritizing primary data as the main source and secondary data as supporting material. The research aimed to analyze criminal law violations occurring within illegal racing phenomena and to examine law enforcement practices against perpetrators who commit mob violence against police officers at the Sidoarjo Regional Police. Findings reveal that criminal law violations in illegal racing phenomena encompass eight categories: traffic and public order violations, mob violence, gambling, negligence causing injury or death, assault, narcotics and alcohol use, property destruction, and incitement. Law enforcement against mob violence perpetrators proceeds through a systematic mechanism comprising police report registration, issuance of assignment orders, investigation processes pursuant to Articles 170 and 358 of the Indonesian Criminal Code, and case referral to the Sidoarjo District Attorney. In practice, investigators face several obstacles including difficulty in identifying individual perpetrators, lack of willing witnesses, and limited electronic evidence; nevertheless, law enforcement is carried out consistently with the objectives of upholding the law and providing a deterrent effect.